GAMBARAN AKTIVITAS SEDENTARI DAN TINGKAT KECUKUPAN GIZI PADA REMAJA GIZI LEBIH DAN GIZI NORMAL - Sofia Rahma Pramudita; Siti Rahayu Nadhiroh (Universitas Airlangga, 2017)
Sedentary activity is an activity that requires very low energy expenditure, such as sitting or lying down while watching television, playing electronic games, and reading that can cause negative effects on health. One of the negative impactis increasing risk for obesity. The purpose of this study was to describe the nutrition adequacy level and sedentary activity among overweight and normal adolescent. This research was descriptive study with cross-sectional design. Thesample was 70 students of SMPN 3 Gresik which divided into two groups based on their nutritional status, overweight or normal with 35 samples in each group. Data of nutrient intake, sedentary activity, and measurements of height and weight obtained from questionnaires and direct interview with respondents. Research showed that majority of overweight adolescent, had an energy and carbohydrate adequacy levels more than 77% of RDA compared to normaladolescent. Overweight and normal adolescents have a similar protein and fat adequacy level. Overweight adolescents had greater sedentary activity level the normal one. Majority of overweight adolescent have higher adequacy levelof energy, carbohydrate, and sedentary activity than normal adolescent. Reducing consumption of sweet, fatty foods, increase consumption of fruits and vegetables, also increase regular physical activity need to be done by the respondent